Pengaruh Kepemilikan Institusional, Kepemilikan Manajerial, Komite Audit dan Ukuran Perusahaan Terhadap Penghindaran Pajak Pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia - Ruslan Ahmad; Ardiansyah Halim (Insan Cita Bongaya Research Journal, 2023)
This study aims to determine and examine the effect of Institutional Ownership, Managerial Ownership, Audit Committee and Company Size on Tax Avoidance in Banking Companies listed on the Indonesia Stock Exchange. Data collection uses secondary data obtained from financial reports accessed through www.idx.co.id. by using purposive sampling technique. The population in this study are banking companies listed on the Indonesia Stock Exchange for the 2021-2022 period, totaling 47 companies. However, the samples used in this study were 25 companies with 50 financial statements. The method used to analyze the data is multiple linear regression analysis. The results showed that partially institutional ownership has a negative effect on tax avoidance, managerial ownership has a positive effect on tax avoidance, audit committee has a negative effect on tax avoidance, and firm size has a negative effect on tax avoidance. Simultaneously institutional ownership, managerial ownership, audit committee and company size have a significant effect on tax avoidance in banking companies.